Cerebral metastases of malignant mesothelioma. Issue 2 (6th February 2022) - Bathini, Abhijith; Kusyk, Dorian M; Stabingas, Kristen; Kujawski, Brandon; Ahn, Janice; Williamson, Richard
Abstract: Malignant pleural mesothelioma represents a rare etiology of lung cancer metastasis to the brain. Neurologically symptomatic presentations are extremely rare as these metastatic lesions are detected in the late stages of the disease. Despite many highly heterogenous treatment techniques reported in the literature, overall survival is poor. A 72-year-old male with a history of mesothelioma presented with recurrent episodes of altered mental status, confusion and expressive aphasia. Imaging indicated a large hemorrhagic, enhancing lesion in the anterior left frontal lobe resulting in midline shift of 6 mm. He underwent a left frontal craniotomy for resection, after which he had complete resolution of symptoms. The resected mass was metastatic high-grade malignant mesothelioma. On a 1-month follow-up, new lesions in the bilateral frontal lobes were discovered, and despite undergoing adjuvant stereotactic radiosurgery, the right one grew significantly, causing notable mass effect. The patient successfully underwent a right craniotomy for resection.